Importance of collaboration and contextual factors in the development and implementation of social participation initiatives for older adults living in rural areas. (23rd July 2021) - Levasseur, Mélanie; Routhier, Sonia; Demers, Karine; Lacerte, Julie; Clapperton, Irma; Doré, Chantal; Gallagher, Frances
Abstract: Introduction: To encourage isolated and vulnerable older adults to accomplish meaningful social activities, occupational therapists and other healthcare workers must collaborate with community organisations and municipalities to develop and implement initiatives fostering social participation. In a rural Regional County Municipality in Quebec (Canada), four social participation initiatives were selected and implemented: (1) Benevolent Community, (2) urban transportation system, (3) creation of a website on social participation activities, and (4) social participation workshop. Little is known about contextual factors such as the structures and organisations, stakeholders, and physical environment that influence the development and implementation of such initiatives. Methods: Led by an academic occupational therapist, an action research to implement social participation initiatives was initiated by community stakeholders. The 26 stakeholders were involved in a Management and Partnership Committee, two focus groups and an interview with a trainer, which documented and analysed contextual factors and the implementation process. Findings and discussion: Development and implementation were facilitated by stakeholder collaboration, mission of the community organisations, and stakeholders' shared desire to reduce older adults' isolation and vulnerability. The established partnerships and predefined orientations as well as the leadership, motivation, and professional skills of the stakeholders also fostered the initiatives. Among the challenges encountered, the stakeholders' limited involvement in implementation tasks was attributable to important changes in the key stakeholders' organisations and structures and the number of organisations involved. Difficulty reaching a consensus resulting from the different attitudes, vision, and understanding of the stakeholders delayed the development and implementation of some initiatives. Despite regular meetings between stakeholders, geographic distance limited spontaneous exchanges. Conclusion: This action research highlighted the importance of collaboration and contextual factors in developing and implementing social participation initiatives with community organisations and municipalities.